Resistance Patterns in Drug-Resistant Pulmonary Tuberculosis Patients at Dr. Mohammad Hoesin Palembang Hospital - Muhammad Novran Chalik; Alif Fathurrachman; Linda Andriani; Rouly Pasaribu; Sudarto; Ahmad, Zen; Ahmad Rasyid (Jurnal RSMH Palembang, 2024)
Tuberculosis (TB) is a contagious infectious disease caused by acid-resistant bacteria, Mycobacterium Tuberculosis (MTb). Based on immunity, there are two types of pulmonary TB infection: drug-sensitive and drug-resistant. Based on ATD sensitization tests, MTb resistance types consist of TB that is monoresistant, polyresistant, multidrug resistance (MDR), pre-extensively drug resistant (Pre-XDR), extensively drug-resistant (XDR). Globally, in 2022, there will be an estimated 450,000 cases of DR-TB, but only 161,000 treated. In Indonesia, in 2022, there were an estimated 24,000 cases of DR-TB; only 8,268 were notified and 5,082 cases had started therapy. In this study, conducted with a retrospective descriptive method, during the period 2022 at RSMH Palembang, 92 patients with DR-TB were obtained who received treatment at RSMH Palembang. Of the 92 subjects, the mean age of diagnosis of DR-TB was 44.47 ± 16.5. The most common gender was male 62 subjects (67.4%) and 30 subjects were female (32.6%). Of the 92 rifampicin-resistant patients, there were a total of 39 patients (42.4%) with isoniazid resistance. Among these 39 patients, 21 patients (54%) were primary resistance cases and 18 patients (46%) were secondary resistance cases. The most common type of therapy regimen used was a long-term regimen as many as 68 subjects (74%) and short-term as many as 24 subjects (26%)Primary resistance patterns were obtained in 43 subjects (46.8%) and secondary resistance in 49 subjects (53.2%). Of the 49 secondary resistance subjects, 52 subjects (56.5%) had TB-RR, 33 subjects (35.8%) had MDR-TB, 6 subjects (6.5%) had pre-XDR TB, and 1 subject (1.2%) had XDR-TB. The researcher concluded that the dominant resistance pattern of pulmonary TB cases was secondary resistance, with the results of the drug sensitivity test being TB-RR. However, it should be noted that DR-TB with a primary resistance pattern also has a higher percentage.